Sidewalk saint - DePoy, Phillip (DePoy, Phillip. Foggy Moskowitz series, 2019)
"Florida, 1976. Foggy Moscowitz knows he's having a bad night when he wakes to find a gun pressed to his face. Nelson Roan has busted out of his prison cell and broken into Foggy's house, demanding Foggy finds his eleven-year-old daughter, Etta. But as Foggy searches for Etta, it seems her father is not the only person who wants her found: Canadian mobsters, crazy New York Irishmen, the FBI and even the Seminole elite are all on her trail. But why? Etta has a special gift - and she knows something that certain people would go to any lengths to make sure stays buried in her memory. As Foggy helps Etta to reveal what she knows, he uncovers a sinister plot with tentacles that stretch further and higher than he could ever have imagined ."--Publisher.